Self-Tensioning Feature of Knotless Suture Anchor Provides Reproducible Knotless Fixation Independent of Initial Tension - Athiviraham, Aravind (Orthop J Sports Med, 2021)
BACKGROUND: Anterior cruciate ligament (ACL) reconstruction with suture tape reinforcement has been shown to biomechanically reduce elongation and increase ultimate strength. However, the amount and consistency of the achieved tension after primary fixation using knotless suture anchors remains unclear. PURPOSE: To determine whether initial tensioning of suture tape before fixation with a knotless suture anchor significantly affects final tension of the suture tape. STUDY DESIGN: Controlled laboratory study. METHODS: We secured 15 pairs of Sawbones blocks with predrilled tunnels to a tensile testing machine. Suture tape was inserted through a suspensory fixation button on the representative femoral block and threaded top-down through the base of the tibial block over an attachable button system. The suture tape was attached with a knotless suture anchor in a predrilled and tapped hole on the tibial block under the following pretensioning conditions: (1) slight tension of 5 N, (2) no tension, and (3) initial slack. The suture anchor was inserted as the load-time data were recorded. After initial block testing, a porcine model of 24 tibias was used to test the same pretensioning conditions. The initial loads during anchor insertion and screw-in were measured, as well as final tension. RESULTS: During block testing, no difference in final tensioning was found when comparing the slight-tension, no-tension, and slack groups (42.3 ± 5.3, 37.7 ± 6.4, and 40.2 ± 7.0 N, respectively; P = .528). Similar to block testing, no difference in final tensioning was found when comparing the slight-tension, no-tension, and slack groups using the porcine model (43.64 ± 6.69, 48.09 ± 13.93, and 44.52 ± 6.84 N, respectively; P = .633). CONCLUSION: The final tension of the suture tape construct appears to be reproducible and consistent, independent of the initial tension introduced with suture anchor placement within the tested parameters. CLINICAL RELEVANCE: The results of the current study can help optimize the placement technique of independent suture tape reinforcement for ACL reconstruction, which is a promising strategy to help prevent ACL rerupture, particularly in the early phases of postoperative rehabilitation.